Sustainable Management of High-Impact Non-Native Molluscs and Their Potential Commercial Importance in the Eastern Adriatic Sea - Nerlovic, Vedrana; Mrcelic, Gorana Jelic; Dogan, Alper (Sustainability, 2023)
Molluscs, especially bivalves, play an important role in food production and are the dominant group in mariculture worldwide. They are also an important component of the marine ecosystem, influencing the food web and nutrient cycling, as well as creating and modifying habitats. In the Mediterranean Sea, about 578 non-native species have been reported, including 230 taxa of non-native mollusc species. In most regional European seas, including the Mediterranean, the socioeconomic impacts of high-impact mollusc species have generally been poorly studied, and only a few well-documented cases have been reported. The present study collects scientific information on non-native molluscs in Croatian waters that are classified as high impact according to the European Alien Species Information Network EASIN: one Gastropoda-Rapana venosa-and seven Bivalvia species-Anadara kagoshimensis, Anadara transversa, Arcuatula senhousia, Brachidontes pharaonis, Magallana gigas, Pinctada radiata, and Ruditapes philippinarum. This study aims to fill the gap in the literature on high-impact non-native molluscs in the eastern Adriatic Sea through reviewing the literature on examples from other European seas, focusing on the possibility of commercialization and sustainable management of high-impact non-native molluscs. The invasion of non-native molluscs must be managed appropriately, especially if commercialisation is chosen as a management strategy. Additional management measures must be selected and objectively evaluated, taking into account the specificities, location and feasibility of the proposed measures. The study could help researchers, decision-makers, and the public to address the problems with high-impact species in the Adriatic countries, but also in other regions where the monitoring of high-impact non-native species is still inadequate. In addition to Croatia, the monitoring and management of these species is also important for other countries in the eastern Adriatic: Slovenia, Montenegro and Albania.